2021
DOI: 10.3389/fphar.2021.666502
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Insulin/PI3K/Akt Signaling Pathway and Modulation of Gut Microbiome by Probiotics Fermentation Technology, a Kefir Grain Product, in Sporadic Alzheimer’s Disease Model in Mice

Abstract: Sporadic Alzheimer’s disease (AD) is the most common neurodegenerative disorder with cognitive dysfunction. Remarkably, alteration in the gut microbiome and resultant insulin resistance has been shown to be connected to metabolic syndrome, the crucial risk factor for AD, and also to be implicated in AD pathogenesis. Thus, this study, we assessed the efficiency of probiotics fermentation technology (PFT), a kefir product, in enhancing insulin signaling via modulation of gut microbiota to halt the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 74 publications
1
13
0
Order By: Relevance
“…This state of brain insulin resistance may be the cause of memory loss in diabetic rats. This was in agreement with several studies that have reported memory disturbances in cases of disturbed brain insulin signaling (El Sayed et al 2021 ). Different studies and clinical trials have shown that resveratrol treatment notably lowers blood glucose levels and improves insulin action in type 2 diabetic patients.…”
Section: Discussionsupporting
confidence: 93%
“…This state of brain insulin resistance may be the cause of memory loss in diabetic rats. This was in agreement with several studies that have reported memory disturbances in cases of disturbed brain insulin signaling (El Sayed et al 2021 ). Different studies and clinical trials have shown that resveratrol treatment notably lowers blood glucose levels and improves insulin action in type 2 diabetic patients.…”
Section: Discussionsupporting
confidence: 93%
“…However, the underlying mechanism by which B. breve MCC1274 supplementation activates Akt is still unclear. Several studies have demonstrated that some probiotics elevate Akt phosphorylation [58,59]. However, further investigations are required to understand the mechanism of B. breve MCC1274-mediated activation of the Akt-GSK-3β pathway.…”
Section: Discussionmentioning
confidence: 99%
“…To examine learning and memory, we performed the novel object recognition (NOR) test [ 16 ]. The test is based on animals' innate preference for a novel object, in which mice remembering the familiar object will devote more time exploring a novel one [ 17 ]. Each mouse was placed in a box (without objects) for 5 minutes to adapt to the surroundings (habituation).…”
Section: Methodsmentioning
confidence: 99%